Detecting the South in Fiction, Film, and Television - Starkey, Theresa 1968-; Starkey, Theresa 1968-; Barker, Deborah 1956-; Barker, Deborah 1956- (Book collections on Project MUSE., 2019)
"The mean streets that tough, trench-coated detectives travel are so often associated with urban settings--typically New York or Los Angeles--that audiences can easily overlook the presence of the American South in crime fiction and film noir. Recent years have witnessed a growth in the production and popularity of southern noir and detective narratives, with works such as James Lee Burke's Dave Robicheaux novels and the first season of True Detective attesting to the powerful impact of the southern imaginary on the genre"